Neuron-glia crosstalk in neuronal remodeling and degeneration: Neuronal signals inducing glial cell phagocytic transformation in Drosophila. - Boulanger, A.; Dura, J.M. (BioEssays, 2022)
Neuronal remodeling is a conserved mechanism that eliminates unwanted neurites and can include the loss of cell bodies. In these processes, a key role for glial cells in events from synaptic pruning to neuron elimination has been clearly identified in the last decades. Signals sent from dying neurons or neurites to be removed are received by appropriate glial cells. After receiving these signals, glial cells infiltrate degenerating sites and then, engulf and clear neuronal debris through phagocytic mechanisms. There are few identified or proposed signals and receptors involved in neuron-glia crosstalk, which induces the transformation of glial cells to phagocytes during neuronal remodeling in Drosophila. Many of these signaling pathways are conserved in mammals. Here, we particularly emphasize the role of Orion, a recently identified neuronal CX3 C chemokine-like secreted protein, which induces astrocyte infiltration and engulfment during mushroom body neuronal remodeling. Although, chemokine signaling was not described previously in insects we propose that chemokine-like involvement in neuron/glial cell interaction is an evolutionarily ancient mechanism.